Exploring the possibilities of using in vitro model for neuropathic pain studies - Mohammed Izham, Noor Aishah; Siew, Jasmine Min Chia; Kaswan, Nur Khalisah; Sukirthalingam, Kavitha; Vidyadaran, Sharmili; Bharatham, Hemabarathy; Sulaiman, Mohd Roslan; Perimal, Enoch Kumar (Neurotak Publishing, 2022)
Establishing experimental models to study neuropathic pain has been challenging due to the complex mechanism underlying the condition. Although in vivo models have been useful in the observation of behavioural pain responses, it should be acknowledged that species-to-species variance can lead to differences in terms of molecular mechanism and genetic expression. The study of molecular and signal transduction of neuropathic pain using in vivo models faces limitations due to ethical considerations involving pain induction in animals and the intricacy of molecular interactions in the pathophysiology of the condition. Hence, developing relevant in vitro models to study neuropathic pain is important, as it considers the physiological microenvironment and reduces the use of experimental animals. Several considerations should be taken into account in developing an in vitro model of neuropathic pain, including the use of either primary culture of cell lines with considerations to their origins; human or animal, the method of neuropathic pain-like induction and the relevant assays to assess pain. This review recapitulates previous research employing in vitro models in investigating the molecular mechanism of neuropathic pain, intending to provide an alternative to the growing concerns on in vivo neuropathic pain models.